2021
DOI: 10.1126/science.abb5920
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplant promotes response in immunotherapy-refractory melanoma patients

Abstract: The gut microbiome has been shown to influence the response of tumors to anti–PD-1 (programmed cell death–1) immunotherapy in preclinical mouse models and observational patient cohorts. However, modulation of gut microbiota in cancer patients has not been investigated in clinical trials. In this study, we performed a phase 1 clinical trial to assess the safety and feasibility of fecal microbiota transplantation (FMT) and reinduction of anti–PD-1 immunotherapy in 10 patients with anti–PD-1–refractory metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
761
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 942 publications
(895 citation statements)
references
References 63 publications
19
761
0
17
Order By: Relevance
“…124 Recently, first-in-human clinical trials showed that fecal microbiota transplantation (FMT) improved the efficacies of anti-PD-1 immunotherapy in patients with anti-PD-1-refractory metastatic melanoma, while also reprogramming the gut microbiome. 125,126 As C. butyricum supplementation has been repeatedly shown to improve symptoms related to microbial dysbiosis, Tomita et al retrospectively analyzed the survival of non-small lung cancer patients who received ICB therapy, with or without CBM 588 within 6 months prior to and concurrently with ICB. 127 Taking CBM 588 significantly improved the progression-free survival (PFS) and overall survival (OS) in patients that have been treated with ICB compared to no CBM 588, even in the population that had been exposed to antibiotics prior to ICB.…”
Section: Butyricum In Immune Checkpoint Blockade Therapymentioning
confidence: 99%
“…124 Recently, first-in-human clinical trials showed that fecal microbiota transplantation (FMT) improved the efficacies of anti-PD-1 immunotherapy in patients with anti-PD-1-refractory metastatic melanoma, while also reprogramming the gut microbiome. 125,126 As C. butyricum supplementation has been repeatedly shown to improve symptoms related to microbial dysbiosis, Tomita et al retrospectively analyzed the survival of non-small lung cancer patients who received ICB therapy, with or without CBM 588 within 6 months prior to and concurrently with ICB. 127 Taking CBM 588 significantly improved the progression-free survival (PFS) and overall survival (OS) in patients that have been treated with ICB compared to no CBM 588, even in the population that had been exposed to antibiotics prior to ICB.…”
Section: Butyricum In Immune Checkpoint Blockade Therapymentioning
confidence: 99%
“…Heterologous FMT is the most widely used gut microbiome intervention in clinical settings. Most research so far has focused on the efficacy and safety of FMT (Baruch et al, 2021; Davar et al, 2021; Ding et al, 2019; Tabbaa et al, 2018; Xiao et al, 2020). Several studies reported that heterochronic FMT could result in the transfer of some physiological properties from the donor to the recipient, including lifespan and healthspan (Bárcena et al, 2019; Smith et al, 2017), the germinal center reaction (Keeney et al, 2014), and neurogenesis and behavior (D’Amato et al, 2020; Rinninella et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…combined with an anti-PD-L1 antibody almost abolished cancer growth (Sivan et al, 2015); commensal microbiota with abundance of B. longum, Collinsella aerofaciens, and E. faecium was associated with anti-PD-1 cancer efficacy (Matson et al, 2018); higher microbial diversity and increased levels of Ruminococcaceae in treatment responders and FMT from responders patients to germ-free animals enhanced response (Gopalakrishnan et al, 2018); faecal levels of A. muciniphila directly correlated with anti-PD-1 therapy efficacy and FMT from responders patients to germ-free or antibiotic-treated mice improved treatment efficacy (Panebianco et al, 2018;Routy et al, 2018). Recently, a clinical benefit was reported in a phase I trial with anti-PD-1 refractory metastatic melanoma patients who underwent FMT from donors with complete response after anti-PD-1 monotherapy (Baruch et al, 2020). In another clinical trial comparing outcomes in patients with metastatic hormone receptor positive BC who received eribulin (antitubulin antimitotic agent) with or without pembrolizumab (anti-PD-1 agent), a shift in the abundance of Akkermansia and Faecalibacterium after two cycles of therapy was described.…”
Section: Gut Microbiota and Its Impact On Breast Cancer Treatmentmentioning
confidence: 99%